New distributional record of red palm weevil, Rhynchophorus ferrugineus (Olivier) infesting arecanut in Assam, India - Rabha, Himadri; Chakrabarty, Ranjana; Acharya, G. C. (Journal of Plantation Crops, 2019)
---------------